International aid policy: public disease control and private curative care? - Pierre De Paepe; Werner Soors; Jean-Pierre Unger
Integrating disease control with health care delivery increases the prospects for successful disease control. This paper examines whether current international aid policy tends to allocate disease control and curative care to different sectors, preventing such integration. Typically, disease control has been conceptualized in vertical programs. This changed with the Alma Ata vision of comprehensive care, but was soon encouraged again by the Selective Primary Health Care concept. Documents are analyzed from the most influential actors in the field, e.g. World Health Organization, World Bank, and European Union. These agencies do indeed have a doctrine on international aid policy: to allocate disease control to the public sector and curative health care to the private sector, wherever possible. We examine whether there is evidence to support such a doctrine. Arguments justifying integration are discussed, as well as those that critically analyze the consequences of non-integration. Answers are sought to the crucial question of why important stakeholders continue to insist on separating disease control from curative care. We finally make a recommendation for all international actors to address health care and disease control together, from a systems perspective.